Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/etc.2026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced food intake on toxicokinetics of halogenated organic contaminants in herring gull (Larus argentatus) chicks

Abstract: Abstract-The aim of the present study was to investigate how contaminant exposure and reduced food intake affect tissue distribution and biotransformation of halogenated organic contaminants (HOCs) in Arctic seabirds using herring gull (Larus argentatus) as a model species. Herring gull chicks were exposed for 44 d to cod liver oil containing a typical mixture of contaminants. Following exposure, food intake was reduced for a one-week period in a subgroup of the chicks. Polyclorinated biphenyls, organochlorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…whereas OCs are stored in adipose tissues before being released into the bloodstream during periods of accelerated lipid mobilization (Aas et al, 2014;Bustnes et al, 2010;Findlay and DeFreitas, 1971;Henriksen et al, 1995;Jones et al, 2003;Kelly et al, 2009;Luebker et al, 2002;Routti et al, 2013;Vanden Heuvel et al, 1992;Verreault et al, 2005). Consequently, we posit that PFASs and OCs could target physiological functions through very different modes of action, without mechanistic interlinkage, potentially resulting in mixed or contrasted responses.…”
Section: Some Contrasted Patterns Between Pfass and Ocsmentioning
confidence: 87%
“…whereas OCs are stored in adipose tissues before being released into the bloodstream during periods of accelerated lipid mobilization (Aas et al, 2014;Bustnes et al, 2010;Findlay and DeFreitas, 1971;Henriksen et al, 1995;Jones et al, 2003;Kelly et al, 2009;Luebker et al, 2002;Routti et al, 2013;Vanden Heuvel et al, 1992;Verreault et al, 2005). Consequently, we posit that PFASs and OCs could target physiological functions through very different modes of action, without mechanistic interlinkage, potentially resulting in mixed or contrasted responses.…”
Section: Some Contrasted Patterns Between Pfass and Ocsmentioning
confidence: 87%
“…Previous research shows that birds (including kittiwakes), with high organochlorine burdens generally have poor body condition and are lighter in mass than birds with low organochlorine levels (Henriksen ; Henriksen et al , ; Helberg et al ; Bustnes et al ). When body mass decreases, the lipophilic organochlorines such as oxychlordane, previously stored in adipose tissues, are released into the blood circulation and become very toxic to the whole organism (Henriksen ; Borgå et al ; Nøst et al ; Routti et al ). It is thus difficult to disentangle a potential confounding effect of body mass or a real impact of contaminants on T inc .…”
Section: Discussionmentioning
confidence: 99%
“…week, exhibited contaminant concentrations that were three times higher in liver, plasma, and brain compared to a non-fasted exposed group (Routti et al 2013). Changes in feeding rates and body mass throughout the breeding season have similarly been associated to contaminant concentrations in some seabirds, both those adapted to long fasts or not, including kittiwakes (Rissa trydactyla) (Henriksen et al 1996), and Adélie penguins (Pygoscelis adeliae) and southern fulmars (Fulmarus galacialoides) (van den Brink et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, lipid mobilization during fasting can lead to increased circulating levels of contaminants as they are released from fat stores (Birnbaum 1985). Several studies have reported increased enzyme-mediated liver metabolism of contaminants following fasting, further confirming that increased organismal exposure occurs during these natural food deprivation phases (Helgason et al 2010;Jorgensen et al 1999;Routti et al 2013;Vijayan et al 2006).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation